A Review of Structural and Functional Differences Between Plant and Animal Cell Organell - Nisa, Fadhila Chairul; Bupu, Karolina; Wele, Mery Kristina; Falo, Yohanes Baptis Dela; Wae, Veronika P. Sinta Mbia (Jurnal Biologi Tropis, 2026)
Understanding the dynamic organization of organelles is fundamental to biology, yet traditional perspectives often overlook the complex inter-organellar communication that defines cellular physiology. This systematic review synthesizes thirty peer-reviewed articles (2015–2025) to bridge the knowledge gap between static organelle morphology and modern functional dynamics in plant and animal cells. By employing a systematic literature review (SLR) approach with thematic synthesis, this study identifies that while core organelles are conserved, specialized structures such as chloroplasts and large vacuoles in plants versus centrioles and lysosomes in animals exhibit distinct evolutionary adaptations in redox balance and quality control mechanisms. The analysis further reveals a universal reliance on inter-organellar contact sites and autophagy pathways, suggesting that cellular health is maintained through a highly integrated "organelle ecosystem" rather than isolated units. These findings offer critical insights for advancing cell biology education and provide a theoretical framework for future research in metabolic engineering and stress adaptation in tropical biological systems.